Impact of Teachers’ Mindset, Skills, and Resilience on Teaching Performance - Planos , Ariel Jr.; Estillero, Kim Chester; Depiña, Jessrelle; Evarrola, Rhezar Kent; Parsons, David (Journal of Interdisciplinary Perspectives, 2025)
This study examines the relationship between teachers' mindset, ability-based practices, and adversity quotient in relation to teaching performance. It aims to determine how these factors influence teaching effectiveness and whether demographic characteristics play a significant role. Using a descriptive- correlational research design, data were collected from 108 randomly selected public school teachers through a validated survey questionnaire. Results indicate that teachers’ demographic profiles do not significantly affect their mindset, ability-based practices, or adversity quotient, suggesting that these factors are influenced more by personal traits and experiences. A slight positive association was found between teachers’ mindset and their implementation of ability-based practices, though not statistically significant, implying that other factors may play a greater role. However, teachers with a positive and growth-oriented mindset demonstrated higher resilience in facing challenges, which can enhance their teaching performance. A strong significant relationship was observed between ability-based practices and adversity quotient, indicating that teachers who effectively apply these practices tend to cope better with adversities, leading to improved performance. These findings highlight the importance of fostering a positive mindset and resilience among teachers to enhance their effectiveness.